96.3k views
5 votes
Can someone solve this and show steps? Thank you!!

Can someone solve this and show steps? Thank you!!-example-1
User Khon Lieu
by
6.2k points

2 Answers

5 votes

Answer:

6.6 5/7

Explanation:

apply radical rule: n square a = a 1/n

or apply radical exponent rule: (a^b)^c= a^bc

User Jakub Licznerski
by
5.3k points
1 vote

Explanation:


6 (\sqrt[7]{6} )^(5) \\ \\ = 6 * {6}^{ (5)/(7) } \\ \\ ={6}^{ (5)/(7) + 1 } \\ \\ = {6}^{ (5 + 7)/(7) } \\ \\ = {6}^{ (12)/(7) } \\ \\ \huge \red{ \boxed{ \therefore \: 6 (\sqrt[7]{6} )^(5) = {6}^{ (12)/(7) }}} \\

User Farmaker
by
5.0k points